Vertical and Horizontal Redistribution: The Cases of Western and Eastern Europe - Maurizio Bussolo; Carla Krolage; Mattia Makovec; Andreas Peichl; Marc Stöckli; Iván Torre; Christian Wittneben (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2018)
European countries have the world's most redistributive tax and transfer systems. While they have been well equipped to deal with vertical inequality – that is, fostering redistribution from the rich to the poor – less is known about their performance in dealing with horizontal inequality, that is, in redistributing among socio-economic groups. In a context where individuals may not only care about vertical redistribution, but also about the economic situation of the specific groups they belong to, the horizontal dimension of redistribution becomes politically salient and can be a source of social tensions. We analyze the performance of the 28 EU countries on redistribution across i) age groups; ii) occupational groups; and iii) household types over the period 2007-2014 using counterfactual simulation techniques. We find a great degree of heterogeneity across countries: changes in the tax and transfer system have particularly hit the young and the losers of occupational change in Eastern European countries, while households with greater economic security have benefited from these changes. Our findings suggest that horizontal inequality is a dimension which policy makers should take into account when reforming tax and transfer systems.
Keywords: D31; D63; O15; H20; 330; Inequality; income; redistribution; taxation